Analisis Daya Saing Komoditas Teh Hitam Indonesia di Pasar Global - Kusnaedi, Putri Maudi; Ernah, Ernah (Universitas Galuh, 2024)
ABSTRACTWorld tea consumption increased by 3.5% over the last decade. The black tea commodity is projected to grow by 2% in the next decade. Black tea is one of Indonesia's leading export commodities that has a role in fulfilling the world's demand for black tea. The decline in black tea commodity exports can be a threat to the competitiveness of Indonesian black tea. The decrease in the area of tea plantations due to land conversion has led to a decrease in the volume of tea production. The purpose of this study was to analyze the competitiveness of Indonesia's black tea commodity (HS Code: 090240) in export destination markets, namely Rusia, the United States, China, Germany and Australia, and to determine the relationship between RCA and export value and volume using the correlation test. This research uses secondary data obtained through the Central Statistics Agency (BPS), Food and Agriculture Organization (FAO), International Trade Center (ITC). This study uses data for ten years from 2012 to 2022. The analysis method used is Revealed Comparative Advantage (RCA) analysis and correlation test. The results showed that the RCA value of Indonesian black tea commodities was competitive in the five export destination countries, namely Rusia, the United States, China, Germany and Australia. The RSCA value obtained from the five countries is positive, which means that Indonesian black tea commodities have a comparative advantage in export destination countries. The correlation test shows that the relationship between RCA value and export value and export volume in the United States and Germany is very strong and the relationship is strong in China. However, in Russia and Australia the correlation value is not significant.